Severe hemophagocytic syndrome after intravesical BCG instillation with a fatal outcome - Stojanović, Stevan; Vojinov, Saša; Dimitrić, Žarko; Levakov, Ivan; Jeremić, Dimitrije; Lakić, Tanja (Vojnosanitetski pregled, 2023)
Introduction. Hemophagocytic syndrome (HS) after Bacillus Calmette-Guérin (BCG) immunotherapy is extremely rare in everyday practice. Only three cases of HS have been reported in the world until now. BCG is used for preventing the recurrence of superficial tumors of the urinary bladder. Severe complications after BCG immunotherapy are rarely seen. Case report. A 55-year-old patient was transferred to the Clinic for Urology after the second round of BCG immunotherapy, in bad condition, after transurethral resection of a bladder tumor. Computed tomography of the abdomen and lesser pelvis was performed, which did not indicate any clear signs of organ failure or disease. Antitubercular, antibiotic, corticosteroid, and symptomatic therapies were applied. The achieved effect of therapy was not satisfactory. HS after BCG immunotherapy was suspected. During further hospitalization, the patient’s already severe condition further deteriorated and became more complicated in the form of multiorgan dysfunction syndrome. Death occurred on the sixth day of hospitalization. A urine culture test was performed post-mortem and three months later, it was positive for Mycobacterium xenopi. Conclusion. Secondary HS after BCG immunotherapy is an extremely rare disease accompanied by a severe general condition of the patient, with many life-threatening complications that can lead to death. We have presented a case of severe HS after BCG immunotherapy that caused the death of the patient. This case was unique because, for the first time, the possible causative agent was isolated – Mycobacteria.
Keywords: bcg vaccine; lymphohistiocytosis, hemophagocytic; multiple organ failure; mycobacterium xenopi; urologic surgical procedures